Digital self-construction and identity negotiation: Audience responses to @ragilmahardika on Instagram - Claudia Widiastuti Mo’i; Imanta I. Perangin Angin; Aelsthri Ndandara; Susana C. L Pellu (C-DISC, 2026)
This study examines how digital self-concept is constructed and identity is negotiated through audience responses on the Instagram account @ragilmahardika, owned by Ragil Mahardika, an Indonesian migrant content creator living in Germany. Using a qualitative case study and interpretive content analysis, the study explores identity representation and audience interaction on social media. Data consisted of 35 Instagram posts published between February and July 2025 and followers’ comments. An inductive analysis identified patterns of self-representation and audience engagement. The findings reveal five interrelated dimensions of digital self-concept: migrant achiever, diaspora educator, authentic global self, cosmopolitan lifestyle individual, and self-development- oriented individual. These dimensions show how personal experiences are selectively curated into socially meaningful identities. Audience responses range from supportive and inspirational to informational, identificational, and critical, demonstrating that followers actively interpret, validate, and contest the presented identity. The study argues that digital identity is not produced solely through self-presentation but emerges from continuous interaction between content creators and audiences. Social media therefore functions as a dynamic space where identity is constructed, validated, and negotiated. Theoretically, the study advances the understanding of self-concept as an intersubjective process, while empirically demonstrating how identity practices are shaped within evolving digital environments.